Math And Dosage Calculations For Health Occupations - Dawe Renee A. (McGraw -Hill, 1992)
This text-workbook presents a comprehensive review of mathematics functions as they relate to dosage calculations. It can be used as a math unit in shorter programs or as a supplement or review in longer courses or programs. The text is presented step-by-step and is limited to the skills necessary for dosage calcula-tion. Work-related exercises allow students to practice skills, concepts, and procedures they will use on the job.